Sagittal curve and high metal density in adolescent idiopathic scoliosis - Fernandes,Fabio Araújo (2014)
Objectives: To analyze radiographically the postoperative kyphosis from patients undergoing surgical treatment for AIS with pedicle screws in all vertebrae included in the arthrodesis. Methods: Retrospective study. The following measurements were evaluated: Cobb angle in anteroposterior radiograph of the three curves (proximal thoracic, main thoracic, and lumbar), Cobb angle in the lateral view of the two curves: thoracic kyphosis (T5-T12) and lumbar lordosis (T12-S1). Results: Of the 25 patients evaluated preoperatively, four (16%) were hypokyphotic, 20 patients (80%) were normokyphotic and only one (4%) was hyperkyphotic. For hypokyphotic and hiperkyphotic patients a satisfactory correction of thoracic kyphosis was obtained in 100% of cases, which was preserved in the final result. The same pattern of thoracic kyphosis was observed for all normokyphotic patients throughout the follow-up. Conclusion: Radiographic evaluation of thoracic kyphosis in patients with AIS treated surgically with pedicle screws in all vertebrae showed satisfactory results with respect to the correction of thoracic kyphosis.